Reflecting on the Screen: Documentary Film Festivals and Citizenship Education - Carole Roy; Susan Young (Adult Education Research Conference, 2010)
Collaboration between adult educators and the media have played a significant role in adult education in Canada, leading to the creation of innovative programs in the past. Today, many stories of community struggles and victories do not make the news. Community-based documentary film festivals offer an alternative source of information and provide a community/ solidarity building event that contributes to rebuilding a meaningful public space.